Koronare Herzerkrankung: interventionelle und operative Therapiemöglichkeiten nach Herzstillstand - Behnes, Michael; Mashayekhi, Kambis; Borggrefe, Martin; Akın, Ibrahim (Herz, 2017)
Coronary artery disease (CAD) represents a common structural cause for developing cardiac arrest in older patients, whereas in young adults cardiac arrest is more often caused by cardiomyopathies and cardiac channelopathies. A structural heart disease is known in almost 50% of patients prior to cardiac arrest. The present review outlines current interventional and operative therapeutic options for patients surviving cardiac arrest. The focus is on associations between epidemiological data on the incidence of malignant arrhythmias causing cardiac arrest depending on the presence or absence of CAD. Furthermore, the potential benefits of an early coronary revascularization as well as of a prompt complete coronary revascularization compared to the individual treatment of the so-called culprit lesion only are described. Finally, the advantages of invasive therapies for patients surviving cardiac arrest, such as targeted temperature management and mechanical cardiac assist devices, are elucidated. Cardiac assist devices comprise the use of the intra-aortic balloon pump (IABP) and devices for extracorporeal life support (ECLS) for peripheral and central support of the right and left heart chambers.